1988
DOI: 10.1099/00221287-134-7-1977
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Ligand Complexes of Platinum(II) as Curing Agents for pBR322 and pBR329 (ColE1) Plasmids in Escherichia coli

Abstract: The mixed-ligand complexes of platinum(II) [Pt(Gly)(uracil)Cl2].H2O and [Pt(His)(adenine)]-Cl.2H2O eliminated multicopy plasmids with the ColE1 origin of replication in Escherichia coli with 100% frequency. However, plasmids of the IncF1, H1 and X groups were totally refractory to these agents under similar conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Planar molecules serve as good intercalating agent. An earlier report proposed that Cis dichlorodiamine platimum (II) chloride by virtue of its planar structure probably acts as an intercalating agent and cured ColE1 plasmids from E. coli 26 . Because PtNPs used in the present study were spherical, as evidenced by TEM imaging (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Planar molecules serve as good intercalating agent. An earlier report proposed that Cis dichlorodiamine platimum (II) chloride by virtue of its planar structure probably acts as an intercalating agent and cured ColE1 plasmids from E. coli 26 . Because PtNPs used in the present study were spherical, as evidenced by TEM imaging (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier report has shown that Cis dichlorodiamine platimum (II) chloride but not platinum salt K 2 PtCl 4 was effective in curing E. coli of high copy number plasmids and the authors had proposed square planar nature of the compound facilitates its interaction with supercoiled/nicked plasmid DNA as an intercalating agent, thereby preventing plasmid replication and concomitantly for the loss of plasmid during segregation to daughter cells 57,58 The same group also reported mixed ligand complexes of Platinum (II) were effective in curing Col E1 plasmids from E. coli 26 . In the present study, PtNPs were spherical (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of using nanoparticles is that their antibacterial action can be maintained for an extended period of time with no loss in stability (Cheow and Hadinoto, 2014). Platinum and copper nanoparticles are instrumental in the elimination of resistance plasmids as they interact with the supercoiled plasmid DNA or with topoisomerases involved in replication, transcription, and recombination processes, ultimately leading to elimination of the plasmids (Lakshmi et al, 1988;Lakshmi and Polasa, 1991;Antonoglou et al, 2019). Copper nanoparticles have also been used in plasmid DNA degradation experiments as well as for blocking plasmid conjugation (Chatterjee et al, 2014;Klumper et al, 2017).…”
Section: Chemical Strategies For Removing Mgesmentioning
confidence: 99%
“…Keeping in view the MIC of TMP, three different concentrations of TMP were selected and applied in combination with different temperatures and pH conditions. Plasmid loss/deletion rates have also been reported to be governed by the type of substrate and pH of growth medium (Lakshmi et al, 1988(Lakshmi et al, , 1989Saint and Venables, 1990). Different combinations of TMP conc.…”
Section: ) ----------------------------------------------------------mentioning
confidence: 99%
“…In the absence of a universally effective curing agent, combinations of different physical and chemical curing agents may be examined for their curing efficiency. Treatment of bacterial strains with various curing agents could promote plasmid loss (Stanisich, 1988;Lakshmi et al, 1988;Saint and Venables, 1990;Debbia, 1992;Crosa et al, 1994). Yasmin and Hasnain (1996) have reported TMP as a successful curing agent, hence curing was accomplished with it.…”
Section: ) ----------------------------------------------------------mentioning
confidence: 99%